'Etc. Etc.': Replicating the 'Exotic' Body on the Nineteenth-Century British Stage. Issue 24 (12th May 2017) - Morosetti, Tiziana
It has been said that 'melodramatic music, just as melodramatic incidents, characters, and dialogue, could be readily assembled from ready-made parts, even as mosaics are fashioned from ready-cut chips of coloured tile'. The trend to borrow from a variety of sources, far from pertaining exclusively to melodrama, is a recurrent feature of nineteenth-century theatre. Increasing competition between venues meant that playwrights had to provide yet more spectacular pieces at very short notice, therefore they recycled elements already known to be attractive to audiences. Stock representations of foreign cultures and of 'exotic' bodies in particular tended to migrate from one production to the other — sometimes being literally reused, creating a general incongruity of details. It was in some cases even sufficient for stage directions to refer to what was arguably a common knowledge of 'exotic' types to see them realized on stage, the employment of 'etc. etc.' in playbills, manuscripts, and acting editions of plays standing for a broad range of specific details. My argument in this article is that the accumulation and replication of elements across performances and genres eventually exposed the fictionality of the Other on stage, potentially affecting the audiences' suspension of disbelief, and complicating political readings of nineteenth-century theatre. Whereas the use of 'etc. etc.' indicates the existence of a shared understanding of what was expected of the Other when it came to their portrayal on stage, the accumulation and consequent incongruity of details may suggest a contradictory idea: were audiences to believe what they saw, and, if so, to what extent could the repetitive representation of the exotic as the result of layered discourses work as political commentary on the contemporary world?